Overexpression of Parkin promotes the protective effect of mitochondrial autophagy on the lung of rats with exertional heatstroke - Ran Meng; Zhengzhong Sun; Ruxue Chi; Yan Gu; Yuxiang Zhang; Jiaxing Wang (Journal of Intensive Medicine)
Background: The roles of the Pink1/Parkin pathway and mitophagy in lung injury during heat stroke remain unclear. In this study, we investigated the role of Pink1/Parkin-mediated mitophagy in acute lung injury (ALI) in rats with exertional heat stroke (EHS). Methods: Sixty Sprague Dawley rats were randomly divided into control (CON), control + Parkin overexpression (CON + Parkin), EHS, and EHS + Parkin overexpression (EHS + Parkin) groups. Parkin was overexpressed by injecting an adeno-associated virus carrying the Parkin gene into the tail vein, and a rat model of EHS was established. Pathological changes in the lung tissue were analyzed using microcomputed tomography (micro-CT), and the lung coefficient and pulmonary capillary permeability were measured. Enzyme-linked immunosorbent assay were used to determine the levels of interleukin-6 (IL-6), IL-1β, and tumor necrosis factor-α, and reactive oxygen species. The morphology of mitochondria in type Ⅱ epithelial cells of lung tissue was observed using transmission electron microscopy; and the apoptosis of lung tissue, the level of mitophagy, and the co-localization of Pink1 and Parkin were determined using immunofluorescence. The expression of Pink1, Parkin, mitofusin-2 (MFN2), phosphatase and tensin homolog (PTEN), PTEN-L, p62, and the autophagy marker microtubule-associated protein 1 light chain 3 (LC3) in rat lung tissue was measured by Western blotting, and the ratio of LC3II/LC3I was calculated. Results: Compared with the EHS group, the survival rate of rats in the EHS + Parkin group was significantly higher. Their lung coefficient and pulmonary vascular permeability decreased and the pathological changes were significantly alleviated (P <0.05). Their levels of inflammatory factors and reactive oxygen species were significantly decreased (P <0.05), and the degree of mitochondrial swelling in pulmonary type II epithelial cells was alleviated. The apoptosis of lung tissue was alleviated, the colocalization of Pink1 and Parkin, LC3 and Tom20 was enhanced, and the ratio of LC3-II/LC3-I increased. The expression of Pink1, MFN2, PTEN-L, and p62 decreased, whereas the expression of PTEN was not significantly different from that in the EHS group (P >0.05). Conclusion: Pink1/Parkin-mediated mitophagy dysfunction is one of the mechanisms underlying ALI in rats with EHS, and activation of Parkin overexpression-mediated mitophagy can alleviate ALI caused by EHS.